The equity implications of exposure to industrial livestock operations - Kay Jowers; Yu Ma; Christopher Timmins (PLoS ONE, 2026)
Concentrated animal feeding operations, particularly hog and poultry farms, have expanded rapidly in North Carolina in recent decades. The air and water pollution they generate cause many environmental and health problems for local communities [40 CFR sec. 122.23(b); US Government Accountability Office (2008)]. Combining farm-level data with address- and household-level data on race and income in North Carolina, we non-parametrically describe exposure to hog and poultry CAFOs by race-income characteristics. We further examine the differences in exposure by household water sources – private wells versus community water systems. Results show strong evidence of disproportionate exposure for low-income Hispanic relative to white households. This exposure gap falls with income, but the gap between African American and white households rises with income, particularly in the case of hogs. These gaps in exposure are larger for those households dependent upon private wells.